Stretch-Shortening Cycle Performance and Muscle-Tendon Properties in Dancers and Runners - Rice, P. E.; Nishikawa, K.; Zwetsloot, K. A.; Bruce, A. S.; Guthrie, C: D.; Nimphius, S. (Journal of Applied Biomechanics, 2021)
The purpose of this investigation was to elucidate whether ankle joint stretch-shortening cycle performance, isometric and isokinetic plantarflexion strength, and maximal Achilles tendon force and elongation differ between dancers, endurance runners, and untrained controls. To differentiate between dancers, endurance runners, and controls, the authors measured maximal Achilles tendon force and elongation during isometric ramp contractions with ultrasonic imaging, maximal isometric and isokinetic plantarflexion strength with dynamometry, and stretch-shortening cycle function during countermovement hopping and 30-cm drop hopping with a custom-designed sled. The Achilles tendon of dancers elongated significantly (P = .05) more than runners and controls. Dancers were significantly stronger than controls during isometric contractions at different ankle angles. Concentric and eccentric strength during isokinetic contractions at 60°·s-1 and 120°·s-1 was significantly higher in dancers and runners than controls. Dancers hopped significantly higher than runners and controls during hopping tasks. Dancers also possessed significantly greater countermovement hop relative peak power, drop hop relative impulse, and drop hop relative peak power than controls. Finally, dancers reached significantly greater velocities during countermovement hops than runners and controls. Our findings suggest dancing and running require or likely enhance plantarflexion strength. Furthermore, dancing appears to require and enhance ankle joint stretch-shortening cycle performance and tendon elongation.